High pulse pressure is associated with an increased risk of prediabetes in hypertensive individuals: A retrospective study based on an adult Chinese population. - Zhanxing Wu; Zhongqing Chen; Wenfei Zeng; Ganggang Peng; Zhenhua Huang (PLoS ONE)
Objectives The pulse pressure (PP) is an important factor influencing the outcomes of diabetes. However, the relationship between the PP and prediabetes has been rarely studied and how this association might be impacted by hypertension is not clear. Methods In this study, we retrospectively included 184,252 adults from 32 regions in China, spanning from 2010 to 2016. Cox regression and sensitivity analysis were used to examine the relationship between PP and prediabetes. For the hypertensive population, Cox proportional hazards regression and smooth curve fitting were performed to explore the non-linear relationship between PP and prediabetes. A two-stage Cox proportional hazards regression model was used to determine the inflection point of PP in relation to the risk of prediabetes. Results After adjusting for confounding factors, we found a positive association between PP and prediabetes (HR: 1.11, 95% CI: 1.03-1.19, P = 0.0045). However, we observed that this relationship was not significant in the normal blood pressure group (HR: 1.06, 95% CI: 0.94-1.18, P = 0.3529). We also found a non-linear relationship between PP and the risk of prediabetes in hypertensive individuals. The inflection point of PP was 31 mmHg. When PP ≥ 31 mmHg, there was a positive association with the risk of prediabetes (HR: 1.22, 95% CI: 1.04-2.08, P <0.0001). Conversely, when PP < 31 mmHg, this association was not significant (HR: 0.83, 95% CI: 0.59-1.15, P = 0.2646). Conclusions This study suggests a non-linear relationship between PP and the risk of prediabetes in hypertensive individuals. Maintaining PP within 31 mmHg is crucial for preventing the occurrence of prediabetes.